Satisfaction in B2B Relationship: Research of reciprocity in the relation between doctors and health plans in the Espírito Santo - Spalenza, André Sarmento; Ronchi, Felipe Andreão; Pelissari, Anderson Soncini (Revista de Administração da UFSM, 2017)
In order to understand the satisfaction in a B2B scenery, it is necessary to have an inside look at how the exchange of values between the sides happens. When talking about satisfaction with healthcare plans, given a research within the databases of CAPES, and ANPAD SCIELO, it is possible to conclude that many studies are related to patient satisfaction with the healthcare plans, but few deals with the satisfaction of doctors, who are also clients in this business to business relationship. Thus, this article analyzes the relationship between physicians and the healthcare plans in the ES, and their perception of value in generating satisfaction. This study was divided into two phases, the first, which was a qualitative study in a focus group format, followed by a quantitative study using a closed questionnaire. The questionnaire was sent via email to all physicians registered at the Regional Council of Medicine of Espírito Santo, in a total of 8581, with a return amount of 236 questionnaire. From that amount, 230 were accredited to at least one healthcare plan. The study employed the Importance-Performance Matrix to classify the perception of accredited doctors, and analysis of GAP's T-Student test and the correlation in data interpretation. GAP's between importance and performance found in all items showed that the performance was lower than expected, however, it was found that in all these items, the process of authorization for clients is what most urgently needs to adapt.